Geochronology and evolution of the Magondi Belt - Glynn, Sarah Maeve (My University, 2017)
The Magondi Belt is a NE-trending Palaeoproterozoic mobile belt, composed of a succession of supracrustal metasediments and minor metavolcanics that is subdivided into the Deweras, Lomagundi and Piriwiri Groups. The Magondi Belt is located in north-west Zimbabwe and is bounded on its eastern flank by the Archaean Zimbabwe Craton and the Pan-African Zambezi Belt to the north. A connection between the Superior and Zimbabwe cratons has previously been made based on similarly aged dyke swarms across the two cratons. This matching magmatic barcode implies that the Superior and Zimbabwe cratons rifted away from one another circa 2.26 Ga based on the ages obtained for the Deweras lavas and the Chimbadzi Hill mafic intrusion. It was into this continental rift margin that the Magondi Supergroup sediments were deposited. The majority of the detrital and xenocrystic zircon ages from the Deweras Group are Archaean (2.86 to 2.63 Ga, with some inherited grains as old as 3.34 Ga); although a maximum depositional age of circa 2.29 Ga for the Deweras Group sedimentary rocks has been determined. Unconformably overlying these sediments, within an environment gradually transitioning from a passive margin into a back-arc basin environment, is the Lomagundi Group. These shallow marine sediments are then followed by those of the Piriwiri Group, deposited within a deeper water environment. Deposition of these two groups is constrained between 2.20 and 2.16 Ga, but may have continued up until the termination of the Magondi orogeny circa 1.99 Ga. According to the currently accepted model, the Magondi orogeny is the result of the Zimbabwe Craton colliding with an unknown continental mass, “Terra Incognita”, resulting in the formation of a Palaeoproterozoic Andean-type magmatic arc along the western margin of the Zimbabwe Craton (the arc is typified by the 2.06 - 2.02 Ga granites and gneisses of the Dete-Kamativi Inlier), which was subsequently thrust over the margin of the Zimbabwe Craton, the consequence of which was a Himalayan-style collision that resulted in high-grade metamorphism and the formation of collisional granitoids (e.g. the Hurungwe Granite) circa 1.99 Ga ago. It has also been established that the Dete-Kamativi Inlier, which flanks the western margin of the Zimbabwe Craton, is an extension of the Magondi Belt. Detrital zircons from paragneisses of the Malaputese Formation have ages ranging from 2.8 to 2.5 Ga, with the youngest grains constraining the maximum depositional age to be around 2.3 Ga. Thus, in terms of age and lithology, the correlation of the Malaputese Formation with the Deweras Group (maximum age of 2.29 Ga) is permissible. A south westward extension of 2.06 - 2.02 Ga granitoids – emplaced during the Magondi orogeny – is indicated by a number of localities in north-eastern Botswana and is believed to also be related to the Palaeoproterozoic magmatic arc. This study has recorded the first evidence of Archaean-aged basement within the Dete-Kamativi Inlier. Two orthogneisses with ages of 2.76 and 2.69 Ga provide strong evidence to suggest that the western margin of the Zimbabwe Craton may extend further to the west than previously recognised. It has also been confirmed, based on the recurrence of ~2.64 Ga aged zircons, in addition to older inherited grains ranging from 3.34 to 2.72 Ga, that the crust below the Magondi Belt is Archaean in age. This is not so, however, for the high-grade gneisses in the northern reaches of the Magondi Belt. It has been previously suggested that these supposed basement granites and gneisses represent an Archaean orogeny, but they are in fact Palaeoproterozoic in age, as represented by the syn-to-post-tectonic 2.02 Ga Hurungwe orthogneiss and the 1.95 Ga Kariba Granite. Additionally, a second, 1.96 Ga, orthogneiss contains zircons with younger metamorphic overgrowth rims that are Pan-African in age (545 Ma) and are attributed to the collision between the Kalahari and Congo cratons in the Neoproterozoic. It is therefore apparent that there is not enough evidence to support the existence of an Archaean “Hurungwe orogeny”. The Magondi orogeny was the heat source for a widespread mineralisation and metamorphic event between 2.15 and 2.03 Ga, based on titanite and apatite ages from samples of the Archaean Copper King and Copper Queen Domes within the Magondi Belt. There is also evidence of a second, younger, mineralisation event, which primarily affected both the Dete-Kamativi Inlier and the Choma-Kalomo Block (south east Zambia). U-Pb data on columbite-tantalite grains (corroborated by 40Ar-39Ar dating of mica separates) from tin-bearing pegmatites within both the Choma-Kalomo Block and the Dete-Kamativi Inlier indicates that mineralisation occurred simultaneously within these two terranes between 1.06 and 0.98 Ga. The similarities (particularly with regards to mineralisation), between the Choma-Kalomo Block and the Dete-Kamativi Inlier imply that these two terranes had a shared history, potentially as far back as the Palaeoproterozoic, but were certainly juxtaposed by 1.06 Ga when the pegmatites were emplaced. The previously undated metasediments of the Choma-Kalomo Block have revealed an abundant Palaeoproterozoic component (2.04 - 1.86 Ga), contradicting the prevailing understanding that the Choma-Kalomo Block is solely Mesoproterozoic in age (on account of the granitoids, which were previously dated at 1.37 and 1.18 Ga). The Choma-Kalomo Block was also thought to constitute an exotic terrane with respect to the neighbouring Dete-Kamativi Inlier and Archaean Zimbabwe Craton. Based on the geochronology presented here, a new model is proposed whereby the thinner lithosphere beneath the Choma-Kalomo Block is either a primary feature or one that resulted from subduction erosion and delamination processes associated with the formation of multiple continental margin magmatic arcs.
A thesis submitted to the Faculty of Science at the University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in Geology. Johannesburg 2017.
Keywords: Geology--Zimbabwe; Magondi Mobile Belt (Zimbabwe)